Identity and parent-child relationship representations of Nezha: From cultural narrative to case conceptualization - Guo, Ruitong; Li, Xianghui (Culture & psychology, 2023)
Objective Based on the assumption that the cultural image at the level of experience is the collective and individual psychological reality expressed by cultural narrative and individual narrative, to study the timeless Tales of Nezha (“Natch”) in China as an experiential cultural image of child development and parent-child relationship. Method We adopted the narrative analysis method which focused on qualitative content analysis, covering religion, folklore, literature, entertainment, education and other fields. Result Our exposition articulates a cultural narrative framework of diachronic and contemporary cultural image of “Nezha”, the iconic child deity. This framework refers to our academic research discipline of describing the image characteristics, plots and interpersonal relationship, and conceptualizing the theme as psychological meaning units of personal identity and parent-child relationship. By analogizing and comparing this framework with the “Nezha” of personal narratives in consultation, we found the interactive clues of the case’s identity and parent-child relationship. We then combined these with specific elements unique and particular to each individual case in order to achieve a meaningful case conceptualization. This process enabled us to apply psychotherapeutic intervention at opportune moments during a counselling session. Conclusions The cultural image emerging from the counseling is not only a personal narrative of resource and a tool for the client to externalize the problem and identity representation, but also a cultural narrative reference point for the counselor to understand the case and to engage in further in-depth work. The personal narrative qualitative data can be obtained by referring to four dimensions: external—internal, event—image, narrative—interpretation, and experience—reflection. With the narrative identity of client, the “Nezha” of personal narrative led to the theme that parent-child relationship impedes the development of personal identity. The counselor was thereby enabled to construct a new meaning and new identity with the client by providing appropriate information and knowledge of the cultural narrative.